KENDALA PENGEMBANGAN BIOMASSA DARI LAHAN HKm KPH RINJANI BARAT - Mimin Aminah; Gelar Satya Budhi (Pusat Studi Pembangunan Pertanian dan Pedesaan (PSP3), 2021)
Forest energy on HKm land in West Lombok KPH can basically be developed by reducing obstacles encountered. These constraints include the tightness of SKAU, long timber harvest time, lack of market guarantees, competition for land for agricultural crops, disturbance of daily needs, and lack of mastery of technology. The results of ISM processing show that the obstacles needed firstly to be addressed are strict SKAU and mastery of technology; following with competition for agricultural land, and subsequently disturbance of daily living needs, insufficient market guarantees, and long harvest time. In order to conquer the initial constraints, namely the tightness of SKAU and the lack of technology. There is a need to provide SKAU without reducing supervision factor for security. At the same time, it is important to transfer technology with a pilot project.